1978
DOI: 10.1037/h0081547
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of cultural differences and language use: A field study in a bilingual environment.

Abstract: A field study was designed to examine the role of perceived cultural differences and patterns of language use regarding intergroup relations in Quebec. The participants were 90 francophone and anglophone executives who were involved in a special three-day program requiring intensive interaction and cooperation to complete their task requirements. A questionnaire, administered at the end of the program, focused on participants' beliefs about Francophone and Anglophone differences in approach to and execution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 5 publications
4
12
0
Order By: Relevance
“…The French, on the other hand, placed a significantly higher importance on the values Exciting Life, Equality and Inner Harmony. Thus, the results with a student-based sample reconfirm the reported perceptions held by Francophone managers that Francophones are different from the Anglophones (Taylor, Simard and Papineau, 1978), and that they approach work situations differently from Anglophones (Taylor, Siniard, McKinnan, Bellerose, 1982 Importance Placed on the Job Factors Table 5 presents mean data comparing English and French Canadian students' motivations with regard to six j o b factors for the years 1972, 1978 and 1986. These results are similar t o those reported by Adler and Graham (1987) that whereas French students give higher importance to those instrumental values necessary for managerial success such as C a p a b l e , lmaginative a n d Selfcontrolled, with some of the larger sized but statistically non-significant inter-group differences found for values Ambitious and Logical also going in the same direction, English students gave a higher importance t o the familyoriented values such as Loving, Responsible and Obedient which are necessary for social success.…”
Section: Rokeach Valuessupporting
confidence: 56%
See 3 more Smart Citations
“…The French, on the other hand, placed a significantly higher importance on the values Exciting Life, Equality and Inner Harmony. Thus, the results with a student-based sample reconfirm the reported perceptions held by Francophone managers that Francophones are different from the Anglophones (Taylor, Simard and Papineau, 1978), and that they approach work situations differently from Anglophones (Taylor, Siniard, McKinnan, Bellerose, 1982 Importance Placed on the Job Factors Table 5 presents mean data comparing English and French Canadian students' motivations with regard to six j o b factors for the years 1972, 1978 and 1986. These results are similar t o those reported by Adler and Graham (1987) that whereas French students give higher importance to those instrumental values necessary for managerial success such as C a p a b l e , lmaginative a n d Selfcontrolled, with some of the larger sized but statistically non-significant inter-group differences found for values Ambitious and Logical also going in the same direction, English students gave a higher importance t o the familyoriented values such as Loving, Responsible and Obedient which are necessary for social success.…”
Section: Rokeach Valuessupporting
confidence: 56%
“…McCarrey, Edwards and Jones (1978) noted that whereas French and English managers were somewhat similar on intrinsic job values, the Francophones did put a higher importance on extrinsic job values. That this movement of French towards English may have also taken place in the non-student population is reflected in findings reported by Taylor, Simard and Papineau (1978) and Gosselin and McCarrey (1980). That this movement of French towards English may have also taken place in the non-student population is reflected in findings reported by Taylor, Simard and Papineau (1978) and Gosselin and McCarrey (1980).…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Language convergence between francophone and anglophone bilinguals was demonstrated in a number of empirical studies conducted in Quebec (Bourhis 1984b;Bourhis and Lepicq 1993). Up untU the late 1970s Quebec studies conducted in the work setting showed that more francophone business executives accommodated by speaking English with their anglophone counterparts than did the latter, who tended to maintain English during mixed-group meetings with francophone executives (Taylor et al 1978;Quebec 1972). Studies have also shown that Speakers who converge to their interlocutor may be more favorably perceived on Status and solidarity traits, especially in cases where convergence is to a higher-status language (Genesee and Bourhis 1988).…”
Section: Motivational Factorsmentioning
confidence: 99%